Sudden sensorineural hearing loss and COVID-19 - Awang Hamat, Ain Saffiya; Muhammad Hasram, Izzatul Umairah; Alwi, Husna Sofia; Izanee, Husna Wahdina; Mohd Razali, Najwa; Che Mohd Nassir, Che Mohd Nasril; Ahmed, Mohamed Ayaaz; Alaa Eldin, Amirah Hannan; Md Tajudin, Huriyyah Hamiemah; Jaffer, Usman (Global Academic Excellence (GAE), 2025)
Sudden sensorineural hearing loss (SSNHL) is an auditory condition that happens rapidly and may result in a permanent hearing impairment. Increasing evidence suggests a potential link between SSNHL and viral infections, including COVID-19. This review examines the association between sudden sensorineural hearing loss and COVID-19 by synthesizing past literatures to identify pathophysiological mechanisms, clinical outcomes and management implications. While some studies supported the association between COVID-19 and SSNHL, others report conflicting findings, highlighting the need for further investigation. Hence, understanding this link is pertinent for improving diagnostic and treatment strategies for SSNHL, with broader implications for the post COVID-19 era.